Haute off the press: designer's edition (2010) - Wozniak, Paul, speaker; Colorado State University. Department of Design and Merchandising, producer (Colorado State University. Libraries, 2010)
Colorado State University's Department of Design and Merchandising presents its 2010 Student Apparel Design Show "Haute off the Press: Designer's Edition." This year's event showcases original designs created by students in the Fall 2009 capstone course in the apparel design and production concentration. Students have developed skills in market research and trend forecasting, design and production processes and the marketing of finished apparel lines, all of which were put to use to create the clothing and entire apparel show. The student designers have gained experience developing product technical packages and using computer-aided design programs to assist in pattern drafting, garment sketches, textile designs and websites for their final lines.
Tomboy Touch / Lindsay Flater; S[lente]r / Heather Leigh Designs; Dom / Sarah Hamilton; Rina Designs / Corina Evans; Audaci Enviro / K. LJ; The New Eco Trend / Katia Moncada; Ekka Apparel / Ben Lingle; Cupcake Cuties: a Line for Little Ladies / Mallory Ritter; The Green Button / Allison Ruhmann; RMF / Aleco Katsaunis; Tatami: Yoga Apparel / Caitlin Menhennett; Imperial Russia / Nancy Maxwell; We Love / Wildrose Hamilton; Jaded / Britni Jade Smith; Blooming in the Rain / Dani Rae; Bread & Butterflies / Alyssa Wagner; Frä-lik / Taylor Elizabeth; Cold Smoke / Ron Rod; Embrace Beauty / Lissie Anne.
Produced by the Department of Design and Merchandising, held on Friday, March 29, 2010.
Accessibility features: Unedited transcript.
To request an edited transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Fashion shows